All fours - July, Miranda 1974- (Edinburgh Canongate, 2024)
"The New York Times bestselling author of The First Bad Man returns with an irreverently sexy, tender, hilarious and literary novel about a woman upending her life." [Bokinfo]
Keywords: Begehren; Menopause; All Fours; Kajillionaire; Der erste fiese Typ; MoMa; Biennale; Frank-O’Connor-Preis; unkonventionell; Roadtrip; Weiblicher Körper; Begierde; Zehn Wahrheiten; Es findet dich; Film-Künstlerin; Regisseurin; Millenials; Rachel Cusk; Sheila Heti; amerikanische Literatur; Mutterschaft; Fiktionale Darstellung